The results of phacoemulsification of cataract with different nucleus lens density in patients with zonular weakness (Ukrainian Journal of Ophthalmology, 2026)
One of the most difficult problems of surgery is the remove eye cataract with lens subluxation, especially when there is lens nucleus density. The purpose of this article is to estimate the effectiveness of cataract phacoemulsification with different density of the lens nucleus in patients with lens Zinn ligaments weakness. Materials and methods. 67 patients (72 eyes) with cataract at the age of 46–88 years including 36 women and 31 men were examined. To stabilize the capsular bag position the implantation of the capsular ring was performed according to our proposed method of ring setting. The patients were divided into 2 groups. The first group consisted of 36 eyes with the nucleus lens density of 2–3 grades, the second — 36 eyes with the nucleus lens density of 4–5 grades. Results. The analysis of complication frequency and structure was conducted. Among intraoperative complications in 5.56 % of patients of the second group the posterior capsule was ruptured with the output of vitreous body into the anterior chamber. This type of complication is not registered in patients of the first group. The presence of complicated cataract, particularly in patients with dense lens leads to increase of the surgical trauma. Conclusions. Experience in the application of the proposed method and the results obtained confirm its efficacy and ability to use it in cataract surgery complicated by lens subluxation.
Keywords: phacoemulsification cataract; lens subluxation; capsular tension ring; nucleus density